Proceedings of the conference on prospects in mathematics education in the 1980's (Prime - 80) - Conference on Prospects in Mathematics Education in the 1980's (Prime - 80) (1978 : Alexandria, Virginia) (Washington, DC : Mathematical Association of America, 1978)
40